2010
DOI: 10.1029/2009gc002715
|View full text |Cite
|
Sign up to set email alerts
|

Birth of a volcanic margin off Argentina, South Atlantic

Abstract: [1] Based on a dense grid of multichannel reflection seismic lines we study the evolution of a volcanic rifted margin segment off Argentina. The segment under study is located between 44°S and 41°S. We describe in detail the facies of the extrusive basaltic complexes across the margin. These include single and multiple Inner Seaward Dipping Reflectors (SDRs) with varying architecture along the margin, Outer Highs, and Outer SDR wedges. A detailed interpretation of a transitional zone between the Inner and Oute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
97
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 74 publications
6
97
1
4
Order By: Relevance
“…Finally, along the conjugate Argentine-South Africa margin, seismic reflection profiles acquired by BGR (Argentine margin) were at our disposal. Line drawings from Hinz et al [1999] and Franke et al [2007Franke et al [ , 2010 together with two sets of wide-angle seismic refraction data [Franke et al, 2006;Schnabel et al, 2008] on the Argentine margin and published seismic reflection/refraction profiles on the conjugate South Africa margin [Emery et al, 1979;Brown et al, 1995;Séranne and Anka, 2005;Paton et al, 2008;de Vera et al, 2010;Hirsch et al, 2009] have also been incorporated into our interpretations for this margin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, along the conjugate Argentine-South Africa margin, seismic reflection profiles acquired by BGR (Argentine margin) were at our disposal. Line drawings from Hinz et al [1999] and Franke et al [2007Franke et al [ , 2010 together with two sets of wide-angle seismic refraction data [Franke et al, 2006;Schnabel et al, 2008] on the Argentine margin and published seismic reflection/refraction profiles on the conjugate South Africa margin [Emery et al, 1979;Brown et al, 1995;Séranne and Anka, 2005;Paton et al, 2008;de Vera et al, 2010;Hirsch et al, 2009] have also been incorporated into our interpretations for this margin.…”
Section: Discussionmentioning
confidence: 99%
“…Structures located in onshore Namibia are after Gladczenko et al [1998]. Seawarddipping reflections (SDRs) and related volcanics are from Moulin et al [2005] and Franke et al [2007Franke et al [ , 2010 for South America and Bauer et al [2000] for Africa. "G magnetic anomaly" after Rabinowitz and LaBrecque [1979]; Lin, lineament; WA, West Africa Craton; CC, Congo Craton, DB, Damara Belt; GB, Gariep Belt; KC, Kalahari Craton; CFB, Cape Fold Belt; AMZ, Amazonia Craton; SF, São Francisco Craton; DFOB, Dom Feliciano Orogenic Belt; RDPC, Río de La Plata Craton; VFB, Ventana Fold Belt; GFS, Gastre Fault System; TZ, transfer zone; FZ, fracture zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of HVLC bodies along the South Atlantic rifted margins is well established from seismic and gravity studies (e.g., Bauer et al, 2000;Blaich et al, 2011;Franke, 2013;Franke et al, 2010;Maystrenko et al, 2013;Schnabel et al, 2008), but they have not yet been studied for areal extent and rifting process determination. That is the purpose of the study reported here.…”
Section: K Becker Et Al: Asymmetry Of High-velocity Lower Crust On mentioning
confidence: 99%
“…These reflectors are interpreted to mark the continentocean transition towards an oceanic crust that was developed probably by Aptian time (about 112 Ma). Dating the magnetic anomalies associated with these volcanic wedges provides important insights, suggesting that rifting started in the southernmost basins (Argentina) and advanced northwards by oceanic propagators (Hinz et al 1999;Mohriak 2001;Franke et al 2010).…”
mentioning
confidence: 99%